Serology of paracoccidioidomycosis. II. Correlation between class-specific antibodies and clinical forms of the disease - Biagioni, L.; Souza, M. J.; Chamma, L. G.; Mendes, R. P.; Marques, S. A.; Mota, N. G. S.; Franco, M. (Oxford University Press (OUP), 1984)
Untreated and previously treated patients with paracoccidioidomycosis were studied for: (i) serum levels of total IgG, IgM and IgA immunoglobulins, by radial immunodiffusion and Paracoccidioides brasiliensis (Pb) antibodies, by indirect immunofluorescence; (ii) correlation between their levels with the clinical forms of the disease; (iii) correlation between the serum titres obtained by tube precipitin with those of anti-Pb IgG, IgM and IgA. In the untreated group, serum IgG levels were significantly increased in patients with the more systemic forms of the disease, especially the acute progressive form. Serum IgA levels were significantly increased in all patients with no statistical difference between clinical forms. Serum IgM levels were normal in all patients. Anti-Pb IgG, IgA and IgM were detected in 97·5%, 32·5% and 45·0% of all cases, respectively. There was a sharp tendency towards higher levels of anti-Pb IgG among those with the acute progressive form (83·4%) in relation to the chronic, more localized forms, mixed form (68·0%) and isolated organic form (55·5%). In the untreated and previously treated group sera, there was positive correlation between the level of anti-Pb IgG and positivity for the tube precipitin test, suggesting that the precipitin-type antibodies are of the IgG class. Broadly, the present data demonstrate a polyclonal activation of the humoral immune system in paracoccidioidomycosis, with a positive relationship between serological results and severity of the disease. © 1984.
Keywords: immunoglobulin a; immunoglobulin g; immunoglobulin m; antibody production; etiology; fungus; human; paracoccidioides brasiliensis; polyclonal activation; serology; south american blastomycosis; Adult; Antibodies, Fungal; Antibody Specificity; Female; Fluorescent Antibody Technique; Humans; Immunoglobulin A; Immunoglobulin G; Immunoglobulin M; Male; Paracoccidioidomycosis; Precipitin Tests; Precipitins; Fungi; Paracoccidioides brasiliensis